6,000 miles of fence : life on the XIT Ranch of Texas - Duke, Cordia Sloan (M.K. Brown range life series, 1961)
In 1907 Cordelia Jane Sloan married Robert L. Duke, a ranch hand who had risen to division manager for the 3,000,000-acre XIT Ranch of Texas, the world's largest. An eager observer, she early began the habit of keeping a diary. As time passed, she had the foresight to realize that the sweaty, tired, hungry cowhands with whom she visited were part of a unique phase of American life. What she particularly perceived was that these men would be glamorized and the memory of their work distorted by writers who could sense a pay vein when they saw one.